If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(y + -2) + 8 = 3(y + -4) + -2 Reorder the terms: 8(-2 + y) + 8 = 3(y + -4) + -2 (-2 * 8 + y * 8) + 8 = 3(y + -4) + -2 (-16 + 8y) + 8 = 3(y + -4) + -2 Reorder the terms: -16 + 8 + 8y = 3(y + -4) + -2 Combine like terms: -16 + 8 = -8 -8 + 8y = 3(y + -4) + -2 Reorder the terms: -8 + 8y = 3(-4 + y) + -2 -8 + 8y = (-4 * 3 + y * 3) + -2 -8 + 8y = (-12 + 3y) + -2 Reorder the terms: -8 + 8y = -12 + -2 + 3y Combine like terms: -12 + -2 = -14 -8 + 8y = -14 + 3y Solving -8 + 8y = -14 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -8 + 8y + -3y = -14 + 3y + -3y Combine like terms: 8y + -3y = 5y -8 + 5y = -14 + 3y + -3y Combine like terms: 3y + -3y = 0 -8 + 5y = -14 + 0 -8 + 5y = -14 Add '8' to each side of the equation. -8 + 8 + 5y = -14 + 8 Combine like terms: -8 + 8 = 0 0 + 5y = -14 + 8 5y = -14 + 8 Combine like terms: -14 + 8 = -6 5y = -6 Divide each side by '5'. y = -1.2 Simplifying y = -1.2
| 4x-3(7-x)=7 | | (2xy^2+2y)dx+(2x^2y+2x)dy=0 | | 3x-72-2x=35 | | h=-t^2+2t | | x-429.30=120.44 | | 17.6n-17.28=21.8n-41.8 | | -[3x-(2x+2)]=-5-[3(2x-4)-3x] | | ln(x+4)-ln(x-2)=2 | | 3x+30+27y=0 | | -6(w+1)-w-12=-7(w+4)+10 | | -3(a+8)=a+2(5a-7) | | 20+5x=150 | | 4m+45=61+2m | | I=Crt | | 4-5x=39 | | 4s+20=200 | | -10p-5(4-4p)=6(p-2)-16 | | 5p+7p=72 | | 7+8=28+x | | 0.39=log(x) | | 6x-4=14x-42 | | 48-9x=-27+6 | | 6x-4=14-42 | | 9-4m=m^2-n | | 58-9x=-27+6x | | 6(s-3)=10-2(s+2) | | 2n+5+2n=8n+3-2n | | (14+10)x(3+4)= | | 9x-10+14=-8x-5 | | 81x^4=81x^2 | | 4x+5=-72x+81 | | 9x+2y+17+10x-12y-11= |